IITA, the lead research partner facilitating agricultural solutions to overcome hunger and poverty in subSaharan Africa: the critical role of appropriate soil fertility and land use management - Vanlauwe, Bernard; Sanginga, N. (2015)
For IITA to thrive and meet the expectations of the wider agricultural community in sub-Sahara Africa it must: (i) continue to occupy the Research for Development (R4D) high ground and raise its profile among local and international partners; (ii) conduct rigorous, well-focused research and assure its delivery to end users; (iii) manage its human, physical and financial resources more effectively and (iv) expand its partnership with both the public and private sectors and more convincingly advocate for needed policy change at many levels across the continent. These are challenging goals, and closing the yield gaps of key commodities in a sustainable manner, as referred to in our Refreshed Strategy 2012–2020, requires doubling the current human and financial resources available to IITA over the next eight years. During the past four years. IITA has increased its funding from the $47 million in 2011 to $143 million today and the number of international staff from the 115 to 230. It is making progress with its partners to raise over 11 million Africans out of poverty and redirect over 7.5 million hectares of under-utilised, marginal and degraded lands to more productive and sustainable use, and guided by and contributing to the four System Level Outcomes (SLOs) as defined by the CGIARhreducing rural poverty, increasing food security, correcting under-nutrition, and promoting more sustainable management of natural resources. IITA has prioritised formulation and delivery of its R4D products. As the Dalberg review commissioned by the CGIAR Consortium Board concludes, the CGIAR has fallen short of effectively translating its excellent science into impact on the rural poor. IITA has recently achieved several research breakthroughs from its core research projects that have the potential to greatly improve the lives and livelihood of these clients. Furthermore, IITA is fine-tuning its delivery systems as indicated through the early achievements of our Business Incubation Platform (BIP) and its Aflasafe, Nodumax and GoSeed product lines. IITA is refining its strategy to direct rural youth from diverse competencies toward agribusiness careers through the Youth in Agribusiness (IYA) program. We are engaging the private sector and strengthening our partnership with National Agricultural Research Institutions (NARIs) and regional organisations by establishing and coordinating major platforms such as the West Africa Biosciences platform; the Pan-African Platform for Soil Research for Development and a Regional Research and Training Centre to link climate change with biodiversity and biotic stresses.